OPTIMALISASI KUALITAS LAYANAN UMRAH BERBASIS TEORI PRODUKSI ISLAM: STUDI DI PT AMANINA TOUR & TRAVEL - Herma Puspa Sari; Anis Afifatul Baroroh (Ekonomi Syariah STAI Sangatta Kutai Timur, 2026)
The Umrah travel industry demands service providers who are not only professional, but also oriented to sharia values. This study aims to analyze the application of Islamic production theory in the management of Umrah services at PT Amanina Tour & Travel and examine the company's efforts in optimizing service quality based on sharia principles. The research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study show that PT Amanina Tour & Travel implements the principles of Islamic production, namely monotheism, trust, justice, and transparency, at every stage of service, starting from cost openness, selection of partners who meet halal standards, the implementation of worship guidance, to services during the Umrah trip. Service quality optimization is carried out through employee training, periodic service evaluation, and strengthening a work culture based on Islamic values. The application of these principles has a positive impact on the trust and satisfaction of pilgrims through safe, transparent, professional, and sharia-compliant services. These findings show that Islamic production theory can be an effective foundation in improving the quality of Umrah services while realizing the value of blessings in the implementation of worship travel services.